The suscebility of hipertensive patients to contract COVID-19 and develop a serious form of disease (Research, Society and Development, 2024)
Objective: Establish the relationship between hypertensive patients who contracted COVID-19 and developed severe forms. Methodology: This is an integrative review of the literature carried out in the months of February and March 2024, in the Scielo, Lilacs, MedLine and PubMed databases, using the following descriptors in health sciences: “COVID-19”, “Hypertension” and “Renin-Angiotensin System”, by the Boolean operator AND. In total, 537 studies were found, after the inclusion criteria (articles published between 2019 and 2024, in Portuguese and English) and complete reading, 16 studies were selected to prepare the review. Results: COVID-19 infection causes endothelial dysfunction, exacerbating a pro-inflammatory state. All inflammation causes an increase in renin in the patient's body, accentuating the RAS. Consequently, patients with SAH have a higher concentration of (ACE-II) in the lung epithelia, the SARS-CoV-2 receptor enzyme. Furthermore, the virus inactivates enzymes that are important for reducing the patient's blood pressure. By decreasing ACE II we have an increase in (ACE-I) and this is related to lung injuries and degradation of bradykinin, an important vasodilator and bronchodilator hormone. It is clear that the development of the severe form of the disease in hypertensive patients occurs due to the inflammatory state of the disease, which is exacerbated, such as the imbalance of the RAS due to organ damage. Conclusion: Therefore, any patient with pro-inflammatory conditions tends to have a more severe condition from COVID-19. Concomitantly with hypertension, an increase in ACE-I causes vasoconstriction and bronchoconstriction and a decrease in ACE-II, deregulating other factors that favor thrombogenic events.